Managing the non-profit organization [soundrecording] principles and practices - Drucker, Peter F. (Harper Collins, 1989)
Provides strategies for appraisal, innovation and growth through discussions with top professionals from leading non-profit human services institutions. By being mission focused - rather than procedure focused - Peter Drucker feels it's easier to gauge performance, set standards, evaluate effectiveness and see the "bottom line" when there is no "bottom line".